Collateral times. Issue 3 (3rd July 2019) - Boy, Nina; Gabor, Daniela
Abstract: Today's financial system essentially relies on the pledge of collateral. A closer look at this uniquely cross-disciplinary instrument not only reveals a remarkable absence in the modern disciplines but also a close relationship with money. This connection is brought into theoretical perspective by analysing the role of pledge in three historical configurations. In ancient Greece, symbola and horoi stones emerge as two distinct devices to secure contract that become entwined in seventeenth–eighteenth century pledge-theories of money as witness and object of exchange. Together these throw new light on the contemporary form of shadow money as a distinct marriage of security and safety.